Application of fecal hemoglobin–haptoglobin complex testing for small bowel lesions. (May 2014) - Shiotani, Akiko; Tarumi, Ken-ichi; Honda, Keisuke; Fujita, Minoru; Matsumoto, Hiroshi; Manabe, Noriaki; Kamada, Tomoari; Hata, Jiro; Haruma, Ken
Abstract Objective. Fecal hemoglobin–haptoglobin (Hb–Hpt) complex testing is theoretically superior to immunochemical fecal occult blood test detecting human hemoglobin (Hb), as Hb–Hpt is more stable compared to Hb during passage through the gastrointestinal (GI) tract. The aim was to examine the role of fecal Hb–Hpt complex testing in predicting small bowel lesions detected by video capsule endoscopy (VCE). Materials and methods. Stools from patients undergoing small bowel VCE for obscure GI bleeding (OGIB) without ongoing overt bleeding were included. Two stool specimens were obtained on different days just before VCE to measure Hb–Hpt complex by ELISA and Hb by latex agglutination turbidimetric immunoassay. Results. Seventy-six patients (39 men and 37 women, average age 66 years) with suspected small bowel lesions entered. Median Hb–Hpt complex and Hb levels were significantly higher (p < 0.001) in those with small bowel lesions compared to those without. Using the suitable cutoff points (Hb >10 ng/ml and Hb–Hpt complex >5 ng/ml), the sensitivity and specificity of the Hb–Hpt complex test to predict small bowel lesions were 71.4% and 73.3%, and those of the Hb test were 61.2% and 89.3%. Small bowel lesions were found in 58.3% with only Hb–Hpt complex positive results (15.8% of total subjects) compared to 83.3% when both were positive (55.3% of total). Conclusions. Measuring fecal Hb–Hpt complex in addition to Hb may be useful to predict the presence of small bowel lesions in patients with OGIB.